Impact of Hyperglycemia Duration on Mortality and Ventilator Dependence in Neonatal Intensive Care Unit - Vahideh Banna Zadeh; Gholamreza Khademi; Forugh Rakhshanizadeh; Bahareh Imani; Nooshin Abdollahpour; Majid Sezavar (Mashhad University of Medical Sciences, 2017)
Background: Hyperglycemia is an independent risk factor for mortality in neonatal intensive care units (NICU).Herein, we aimed to investigate the relationship of hyperglycemia duration with mortality and ventilator dependence in infants admitted to NICU.Methods: In this original retrospective study, data was collected between October 2015 and December 2015 from NICU of Dr. Sheikh Children's Hospital in Mashhad, Iran. The studied samples (n=112) were 0-3 month old infants who were admitted to this hospital and were followed up until discharge. Information related to blood sugar was collected based on the samples routinely taken using a glucometer every six hours and were recorded in each patient's blood sugar chart.Results: Of the subjects, 46.4% (n=52) had blood sugar ≥ 126 mg/dl and 53.6% (n=60) had blood sugar ≤ 40-125mg/dl. Mann-Whitney and logistic regression tests were used to analyze the data. In this study, we controlled the effect of confounding variables; a significant association was observed between mortality and duration of hyperglycemia (P=0.002). In addition, a significant association was observed between duration of hyperglycemia and ventilator dependence (P=0.02).Conclusion: Our study showed that the duration of hyperglycemia is positively associated with mortality andventilator dependence in infants admitted to NICU.